2015
DOI: 10.3390/molecules20047000
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Asphyxia: A Review from a Metabolomics Perspective

Abstract: Perinatal asphyxia is defined as an oxygen deprivation that occurs around the time of birth, and may be caused by several perinatal events. This medical condition affects some four million neonates worldwide per year, causing the death of one million subjects. In most cases, infants successfully recover from hypoxia episodes; however, some patients may develop HIE, leading to permanent neurological conditions or impairment of different organs and systems. Given its multifactor dependency, the timing, severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 35 publications
0
42
0
8
Order By: Relevance
“…In newborns with perinatal asphyxia, a small number of metabolomics studies have been published in the literature (22)(23)(24)(25)(26)(27); each of them has depicted the metabolic snapshot of the disease. As recapitulated in a recent review (28), human metabolomics studies have found that the most impaired molecular pathway during perinatal asphyxia and TH are the TCA cycle and the osmoregulation system.…”
Section: Introductionmentioning
confidence: 99%
“…In newborns with perinatal asphyxia, a small number of metabolomics studies have been published in the literature (22)(23)(24)(25)(26)(27); each of them has depicted the metabolic snapshot of the disease. As recapitulated in a recent review (28), human metabolomics studies have found that the most impaired molecular pathway during perinatal asphyxia and TH are the TCA cycle and the osmoregulation system.…”
Section: Introductionmentioning
confidence: 99%
“…In the experimental setting metabolomic studies performed in animal models of hypoxia reoxygenation have shown that oxidative stress associated metabolites strongly correlate with brain injury. The most specific and reliable biomarkers identified have been isoprostanes, neuroprostanes, non-protein bound iron, and 4-HNE proteins adducts [15][16][17]. F2-isoprostanes have been determined to be both biomarkers and mediators of oxidative stress in numerous diseases [18].…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal asphyxia affects some four million neonates worldwide each year, causing the death of one million of them [8]. In most cases, the infants successfully recover from the hypoxic condition, but some patients develop HIE, leading to permanent neurological sequelae, such as seizure disorders, cerebral palsy, cognitive delays, and motor disabilities [6]. Furthermore, in addition to neurologic failure, asphyxia could lead to multiple organ impairment (central nervous system 28%, cardiovascular system 25%, kidneys 50%, and lungs 23%) [9,10] Clinical findings, laboratory examination, aEEG, and MRI in the present three cases showed severe perinatal asphyxia.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases of perinatal asphyxia develop hypoxic ischemic encephalopathy (HIE) and multiple organ impairment, such as disseminated intravascular coagulation and respiratory, liver, heart, and renal failure [6]. Although perinatal asphyxia could potentially lead to CDI, CDI caused by severe asphyxia is very rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation